Pengelolaan Arsip Dinamis di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Pemerintah Kota Surakarta - Kusumawardhani, Arinta; Usman, Ilona Larasati; Wulanjari, Natalia Dharis (Universitas Negeri Padang, 2024)
The Staffing and Human Resources Development Agency of Surakarta City is one of the institutions responsible for managing and developing staffing and staffing information systems. One of the activities of BKPSDM is administrative management. BKPSDM has implemented the archive life cycle as well as possible in its management. This research uses data processing and information collected from interviews and literature studies without measuring instruments or using numbers. The subject of this research is an archivist informant who can explain the current conditions and information about the object of research. Interviews conducted by the author and the archivist of BKPSDM Surakarta City provide results that archive management at BKPSDM Surakarta City is structured in terms of archive life cycle flow but still not optimal in archive management. There were shortcomings in the management aspect of several archive lifelines. Especially in the maintenance and destruction flow. The workforce at BKPSDM Surakarta City does not yet have the awareness to manage archives in an organized and structured manner. In addition, the archive manager in each field has main tasks and functions that do not focus on archives alone, so the archive management of each field has not run optimally. From these problems, the management of dynamic archives in BKPSDM is still not running optimally because human resources, who are archive managers for each field, still do not have the awareness to manage archives properly.